KEPENTINGAN TIONGKOK MEMBERI PINJAMAN LUAR NEGERI KEPADA VENEZUELA TAHUN 2010-2016 - Tiya Anugrah Esa; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains China's policy of providing foreign aid to Venezuela in the economic crisis due to the large foreign debt and falling world oil prices. The strengthening US dollar has been the main cause of the decline in world oil prices over the past few years. In fact, the US dollar was at its highest level in 12 years against the euro, which led to a rise in the US dollar index and falling oil prices. And Venezuela is a country very unprepared for it. As we know that Venezuela depends on their oil sales.The theory used in this research is Neo-liberal is one of the perspectives in International Relations, Neo-liberalism has a pattern of the main driving factor for international cooperation is the international power distribution. And neoliberalism describes the concepts of rationality and prefer to cooperate with institutions and also international organizations to realize their interests. China, which is a very energy-consuming country, is providing overseas aid to Venezuela to meet their growing fuel consumption, as well as to shift US hegemony in VenezuelaKeywords: economic crisis, foreign aid, foreign debt, hegemony